Effects of Herbal Medicine (Gan Mai Da Zao Decoction) on Several Types of Neuropsychiatric Disorders in an Animal Model: A Systematic Review Herbal medicine for animal studies of neuropsychiatric diseases - Su Ran Kim; Hye Won Lee; Ji Hee Jun; Byoung-Seob Ko (Korean Pharmacopuncture Institute, 2017)
Objectives: Gan Mai Da Zao (GMDZ) decoction is widely used for the treatment of various diseases of the internal organ and of the central nervous system. The aim of this study is to investigate the effects of GMDZ decoction on neuropsychiatric disorders in an animal model. Methods: We searched seven databases for randomized animal studies published until April 2015: Pubmed, four Korean databases (DBpia, Oriental Medicine Advanced Searching Integrated System, Korean Studies Information Service System, and Research Information Sharing Service), and one Chinese database (China National Knowledge Infrastructure). The randomized animal studies were included if the effects of GMDZ decoction were tested on neuropsychiatric disorders. All articles were read in full and extracted predefined criteria by two independent reviewers. Results: From a total of 258 hits, six randomized controlled animal studies were included. Five studies used a Sprague Dawley rat model for acute psychological stress, post-traumatic stress disorders, and unpredictable mild stress depression whereas one study used a Kunming mouse model for prenatal depression. The results of the studies showed that GMDZ decoction improved the related outcomes. Conclusion: Regardless of the dose and concentration used, GMDZ decoction significantly improved neuropsychiatric disease-related outcomes in animal models. However, additional systematic and extensive studies should be conducted to establish a strong conclusion.